Magnetoelectric coupling in strained strontium titanate and Metglas based magnetoelectric trilayer - Vivek, S. (2019)
Direct magneto electric coupling is observed with a magnetoelectric coupling coefficient (MECC) of 806 mV cm−1 Oe−1 at 750 Hz in strontium titanate (STO) - Metglas - strontium titanate (STO-Metglas-STO) trilayer thin films with a total thickness of 600 nm. The piezoelectricity in the strained STO layer, which is otherwise a paraelectric material, enabled the sandwiched magneto electric structure to exhibit a fair sub resonant magneto electric coupling. Theoretical models proposed by Bichurin et al. and Hasanyan et al. are employed to calculate the values of MECC at sub resonant condition for the system, which is noted as 853 mV cm−1 Oe−1. The frequency dependence of MECC coefficient is also calculated and the resonance frequency is estimated as 706 Hz.